KONSEP MAQASHID SHARI’AH TENTANG PERAN GANDA TENAGA KERJA PEREMPUAN DALAM PEMIKIRAN EGALITER MUHAMMAD IBNU ‘ASHU - Kammia Rizqa Amalia (Indonesian Journal of Islamic Law, 2018)
This study examines the egalitarian thought of Ibn ‘Āshūr. To limit the scope of the discussion, the author focuses on two main issues: first, how the protection of female workers with dual roles is regulated in Law No. 13 of 2003 on Manpower; and second, how the concept of maqāṣid al-sharī‘ah reflects egalitarian values in the thought of Ibn ‘Āshūr. This research is a library-based study employing content analysis as its analytical method. The primary sources of this study are Ibn ‘Āshūr’s works on maqāṣid al-sharī‘ah and Law No. 13 of 2003 on Manpower, which regulates the protection of female workers with dual roles. The findings of this study show: first, that Law No. 13 of 2003 contains several provisions that protect the dual roles of female workers; and second, that Ibn ‘Āshūr’s egalitarian perspective, viewed through the framework of maqāṣid al-sharī‘ah, is in line with the spirit of protection embodied in Law No. 13 of 2003 on Manpower.